Analisis Sistem Pentanahan di Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Padang - Hambali Hambali; Yeza Permata Sari (Jurnal Teknik Elektro Indonesia, 2021)
The ideal grounding resistance to avoid from lightning strikes is R < 1 Ω . This study aims to measure grounding resistance and analyze the resistance grounding at different depths. The research was conducted in the Integrated Class Building and Chemistry Laboratory Building, Faculty of Mathematics and Natural Sciences, Padang State University (FMIPA UNP). The type of research used is an experiment by direct measurement to measure the grounding resistance at the grounding terminal on the box electrical and measuring ground resistance using solid electrodes with a diameter of 5/8 inches at different depths. Measurements were carried out using the three-point method using an Earth Tester. Based on research conducted, the average value of ground resistance in the Integrated Class Building, Department of Mathematics1and1Science, Padang State University is 1.85 Ω and the average value of ground resistance in the Chemical Laboratory Building is 9.38 Ω. The recommended ground system was installed is grounding single1rod with ground resistance 0.91 Ω at the Integrated Class Building, Faculty of Mathematics and Natural Sciences, Padang State University and R = 0.95Ω at the Chemistry Laboratory Building, Faculty of Mathematics and Natural Sciences. Padang State University.